Analysis of Organophosphorus compound poisoning patients attending CMS-TH, Bharatpur, Nepal - Laudari, S; Patowary, BS (Journal of College of Medical Sciences-Nepal, 2012)
Organophosphorus (OP) compound poisoning is a medical emergency. It is important to know its nature, clinical presentation, severity and outcome in order to take up appropriate measures including proper planning, treatment and prevention. This study was aimed to assess the clinical profile of organophosphorus poisoning. This is a prospective hospital based study conducted at CMS-T.H., Bharatpur, Nepal. The study included 111 patients of organophosphorus poisoning during the period November 2008 to July 2011. The incidence was commoner in females than males with female:male ratio being 1.47:1. Majority of the patients(58.56%) belonged to the age group 16 to 30 years with female predominance(2.25:1). Modes of poisoning were suicidal in the majority (94.59%), accidental in 4.50%. and homicidal in 0.90%. Psychiatric problems were the major precipitating factors. Majority of patients(62.16%) had moderate poisoning (POP scale: 4-7).On admission, dyselectrolytemia and respiratory failure were found in 74.77% and 21.62% respectively.8 patients expired (7.69%). Large amount of OP poison ingestion (>40ml) and increased severity of poisoning (POP scale) were found to have statistical significance with the rate of mortality. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 9-19 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6736